Accessibility, affordability and equity: Assessing 'pro-poor' public transport subsidies in Bogotá. (30th September 2018) - Guzman, Luis A.; Oviedo, Daniel
Abstract: Public transport has claimed a preferential position in recent urban development agendas internationally. Rising interest on inclusive development of cities at different levels of urban policy involves new opportunities and challenges for increasingly urban societies. In cities of the Global South, in addition to institutional and physical challenges for the development of efficient and inclusive public transport, local governments face the challenge of making public transport affordable for a large share of the population in conditions of poverty. In order to meet these challenges, several public transport systems throughout have implemented targeted subsidies for specific social groups such as students, the elderly and people with reduced mobility, and more recently for the poor. The government of Bogotá has implemented a pro-poor public transport subsidy scheme that aims at alleviating the financial burden of poor households for accessing the city's public transport system. This research develops an analysis of the effects of such subsidy from an accessibility perspective using potential accessibility measures to employment opportunities and assess its impact on equity. The research builds on the hypothesis that accessibility is a multi-dimensional construct that can benefit from the decrease in economic as much as gains in time costs. Results from the analysis show that both the current structure of the pro-poor subsidies in Bogotá and alternative scenarios for increasing its coverage are progressive, improving accessibility and equity for those with access to the subsidy. The paper provides valuable insights for the analysis of similar policies in other urban contexts in the Global South. Highlights: Effects on accessibility to income-generating opportunities of the implementation of public transport subsidy. The pro-poor public transport subsidies can reduce the accessibility gaps between better-off and lower income population. Equity metrics are an effective form of evidence for supporting moral arguments related to the reduction of inequalities. Results suggest a relevant potential of pro-poor transport policies, to close the gap between rich and poor.